1997
DOI: 10.1111/j.1399-6576.1997.tb04615.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pressure‐ and volume‐controlled ventilation at different inspiratory to expiratory ratios*

Abstract: Inverse ratio ventilation did not result in improved FRC in comparison to conventional volume-controlled PEEP ventilation. PCIRV allows for a reduction in minute ventilation but the increase in mean airway pressure compromises circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…These results indirectly reflect a reduction in the amount of atelectasis and an improvement in V/Q mismatching in the dependent lung 26,27 . Interestingly, most previous studies of inverse ratio ventilation used a more prolonged I:E ratio than 1:1 and PCV with decelerating inspiratory flow in the supine position 10,11,28 , but our results showed that VCV with only a minimal prolonged I:E ratio could result in improved CO 2 elimination and lower ventilatory requirements during OLV.…”
Section: Discussioncontrasting
confidence: 71%
“…These results indirectly reflect a reduction in the amount of atelectasis and an improvement in V/Q mismatching in the dependent lung 26,27 . Interestingly, most previous studies of inverse ratio ventilation used a more prolonged I:E ratio than 1:1 and PCV with decelerating inspiratory flow in the supine position 10,11,28 , but our results showed that VCV with only a minimal prolonged I:E ratio could result in improved CO 2 elimination and lower ventilatory requirements during OLV.…”
Section: Discussioncontrasting
confidence: 71%
“…These results correspond to the finding that by increasing P mean , gas exchange improved, regardless of the inspiratory flow-wave form (18,19). However, other studies have revealed that with adequate PEEP, the increase of P mean does not further improve Pao 2 but may decrease DO 2 because of a decrease of CO (21,22). However, other studies have revealed that with adequate PEEP, the increase of P mean does not further improve Pao 2 but may decrease DO 2 because of a decrease of CO (21,22).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, P mean increased with V dec when compared with V con . Thus, as suggested by other investigators (21,22), it appears that the increase of oxygenation using PEEP cannot be further improved by PCV with V dec . As a result of the increase of total PEEP from 5 cm H 2 O (ALI) to 8 cm H 2 O (2, 4, and 6 hours) Q S /Q T decreased in both groups.…”
Section: Discussionmentioning
confidence: 69%
“…PC-IRV has been found to improve PaCO 2 more than PCV 1:2[1617] or volume-cycled ventilation with PEEP do. [1617] A crossover study[10] evaluated eight patients with ARDS in whom six hours of volume-controlled IRV was compared with six hours of conventional ventilation showed modest improvement in CO 2 while on IRV. In our study, the PaCO 2 was comparable between groups and no significant adjustment in respiratory rate was needed to keep comparable ETCO 2 and PaCO 2 .…”
Section: Discussionmentioning
confidence: 99%